Tourism Investment, Labor Gains, And Delayed Growth: A Synthetic Control Evaluation Of Indonesia’s DPSP - Sri Ulina Siallagan; Al Muizzuddin Fazaalloh, S.E.,M.E.,Ph.D (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2026)
Indonesia’s Super Priority Tourism Destinations program identifies five regions outside Bali as strategic hubs for concentrated tourism investment. However, rigorous causal evidence of its economic impact remains largely absent from the literature. This study assesses the program’s effect on regional economic growth in North Sumatra and North Sulawesi—the provinces that host Lake Toba and Likupang—using the Synthetic Control Method, complemented by the Mann-Whitney U test to examine changes in tourism-related employment, wages, and output in the accommodation sector. The Synthetic Control results indicate that aggregate regional output in both provinces remained below their respective counterfactual trajectories throughout 2020–2024, with mean treatment effects of -0.0428 log points in North Sumatra and -0.0496 log points in North Sulawesi. In contrast, the Mann-Whitney U test reveals statistically significant increases in tourism-related employment and average wages in both provinces over the same period. This divergence between aggregate and sectoral outcomes constitutes the study’s central finding. The results are consistent with a sequential interpretation of the Tourism-Led Growth Hypothesis, in which labor market adjustments emerge earlier than broader output multipliers, particularly under conditions of early-stage destination development and pandemic-related demand disruptions. These findings extend the Tourism-Led Growth Hypothesis literature to settings shaped by a simultaneous global economic shock and make a methodological contribution by introducing a multi-level evaluation framework for tourism policy assessment.